Telekom Malaysia Retail Outlets: A Study On Consumer's Value Perception - Mahmud, Hamidah (2000)
The study main objectives are basically to assess the customer's expectation on Kedai Telekom, their perceived service quality on Kedai performance, and to identify the determinants of customer satisfaction. The study main focus is to gather key informati